2018
DOI: 10.1111/ahg.12293
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns common and unique to ulcerative colitis and celiac disease

Abstract: Autoimmune diseases like celiac disease (CeD) and ulcerative colitis (UC) show a common genetic background defined by the existence of shared susceptibility loci. We aimed to go deeper into this common genetic background through performing a cross-disease study based on gene expression. We measured the expression of 21 genes located in 13 CeD-UC susceptibility regions, and 10 genes in five CeD risk regions. Determinations were carried out in colon/rectum samples from 13 UC patients (inflamed and uninflamed tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Current experimental data suggested that 5 IBD risk loci, which incorporated genes important for adaptive immune regulation (IL1RL1/IL18R1/IL18RAP, RTEL1/TNFRSF6B, STAT3, and IL2/IL21) and tissue response (LRRC32), were significantly associated with AD [31]. Intriguingly, investigators revealed that AD symptoms in BALB/c mice were alleviated by antagonizing C-C motif chemokine receptor 4 (CCR4), which was significantly increased in UC patients, as well [34][35][36]. Additionally, there are strong signs that C-C motif ligand 17 (CCL17), the chemokine…”
Section: Discussionmentioning
confidence: 99%
“…Current experimental data suggested that 5 IBD risk loci, which incorporated genes important for adaptive immune regulation (IL1RL1/IL18R1/IL18RAP, RTEL1/TNFRSF6B, STAT3, and IL2/IL21) and tissue response (LRRC32), were significantly associated with AD [31]. Intriguingly, investigators revealed that AD symptoms in BALB/c mice were alleviated by antagonizing C-C motif chemokine receptor 4 (CCR4), which was significantly increased in UC patients, as well [34][35][36]. Additionally, there are strong signs that C-C motif ligand 17 (CCL17), the chemokine…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of selected biomarkers in other inflammatory conditions of the small intestine should be investigated, and it would be very interesting to determine which pathways are shared and which are disease specific. In a study of CD and ulcerative colitis, expressions of genes in shared genetic susceptibility loci and specific CD risk loci were investigated and revealed both common and opposite expression patterns in the two diseases 181 .…”
Section: Discussionmentioning
confidence: 99%
“…The efforts made by us and others to characterise gene expression in CD could be summarised into a biomarker profile, based on single biomarkers and/or biological processes, to facilitate CD diagnostics. However, the loss of visualisation compared to the histopathologic assessment is one issue when it comes to gene expression analysis in intestinal biopsies, another is, as mentioned, that gene expression in other diseases of the gastrointestinal tract could show partly the same profile both in the intestine and blood 181 . The need for a reference population to compare with individual gene expressions could make it difficult to implement the method clinically.…”
Section: Discussionmentioning
confidence: 99%
“…(1) SP did not react with SA in a similar reaction condition. (2) The PD concentration in the ultrafiltrate was not changed after the further 24 h incubation of the ultrafiltrate. (3) After the ultrafiltrate was treated in 0.1 M NaOH, the PD concentration did not increase.…”
Section: Drug Distribution In the Gastrointestinal Tract After The Inmentioning
confidence: 95%
“…Although the etiology of ulcerative colitis (UC) remains unclear [1], it is regarded as an autoimmune disease. Additionally, UC is induced by genetic factors or is inherited [2]; however, behavioral and environmental factors also appear to contribute to its onset. UC is a chronic relapsing disease that causes colonic inflammation and complications [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%